Assessing the capability of the corneal blink reflex to display neurological changes following subconcussive head impacts - Osamudiamen S. Ogbeide; Madeleine K. Nowak; Madeleine K. Nowak; Madeleine K. Nowak; Lillian Klemsz; Dena Garner; Keisuke Kawata; Keisuke Kawata (Frontiers in Neurology)
IntroductionThis study examines the capability of detecting neurological changes caused by subconcussive head impacts by analyzing the blink reflex of an individual when they encounter puffs of air as a stimulus.MethodsFollowing attrition and technical issues, 26 participants (15 females, 11 males: age ± SD; 21.3 ± 2.11 years) with at least 5 years of soccer heading experience were included in the final analysis. Participants performed 10 soccer headers with soccer balls projected at a speed of 30 mph. Parameters related to blink reflex, including blink latency, differential latency, number of oscillations, delta 30, and excursions, were assessed by the EyeStat device at pre-heading baseline, and 2-h and 24-h post-heading.ResultsSignificant declines in blink reflex parameters were observed at specific post-heading timepoints compared to baseline. At 24-h post-heading, significant reductions were detected in the overall blink latency (p = 0.0255), the blink latencies of the right eye (p = 0.0411), ipsilateral latency (p = 0.0314) and contralateral latency (p = 0.0434). At 2-h post-heading, significant declines were observed in the overall delta 30 value (p = 0.0053) and delta 30 of the right eye (p = 0.0260). Both delta 30 values returned to baseline by the 24-h post-heading timepoint. No significant changes in the differential latency, number of oscillations, and excursion of the eye were found.DiscussionThese findings suggest changes in the latency and delta 30 of a blink reflex is a viable measure of detection for neurological changes when monitoring subconcussive head impacts.